Implementasi pemasangan label FoP pada Produk Minuman Berpemanis dalam kemasan oleh supermarket: Perbantiangan antara Indonesia dengan Singapura - Naranatha, Atyasa Zefanya; Janisriwati, Sylvia; Putri, Dinda Silviana (Fakultas Hukum Universitas Hang Tuah, 2026)
Indonesia ranks third in Southeast Asia in terms of the population consumption of sugar sweetened beverages (SSBs). The increasing consumption of such beverages has also contributed to a rise in the prevalence of non-communicable diseases (NCDs). The World Health Organization (WHO) recommends a daily sugar intake limit of 50 grams, equivalent to four tablespoons, which has been adopted by Indonesia Ministry of Health. Business actors are required to comply with obligations set out in the Consumer Protection Law. However, nutritional labels are often difficult for consumers to understand, creating an urgency to regulate simpler and more accessible labeling formats. One such simplified format is the Front of Pack Nutrition Labeling (FoPNL). Singapore has regulated and implemented FoPNL on packed products through the Nutri Grade labeling system. In Indonesia, one retail supermarket has started to apply FoPNL system Nutri Grade on sugar sweetened beverage products. There have also been efforts to impose taxes on sugar-sweetened beverages as a strategy to reduce consumption. This research employs a normative juridical method, relying on statutory regulations and their derivatives, as well as literature from books, journal and printed media. The findings indicate that the implementation of Nutri Grade labeling by retailer businesses serves as a form of legal protection to customers.